Software Development with Code Maps. - DeLine, Robert; Venolia, Gina; Rowan, Kael (Communications of the ACM, 2010)
The article discusses the use of diagrams in software development. The authors present a story to illustrate how code maps are developed to illustrate computer architecture. They suggest architecture diagrams are often not specifically connected to codes and may not be task-specific. They describe the use of Code Canvas, a plug-in for Microsoft Visual Studio software, to create an interactive code map. Interviews with software developers suggests that diagrams are used most often to investigate source code, design and debug programs, and serve the information needs of others regarding code.